2018
DOI: 10.1021/acsami.8b07082
|View full text |Cite
|
Sign up to set email alerts
|

Porous ZnO-Coated Co3O4 Nanorod as a High-Energy-Density Supercapacitor Material

Abstract: CoO with a high theoretical capacitance has been widely recognized as a promising electrode material for supercapacitor, but its poor electrical conductivity and stability limit its practical applications. Here, we developed an effective synthetic route to synthesize one-dimensional (1D) porous ZnO/CoO heterojunction composites. Benefiting from the heterostructure to promote the charge transfer and protect CoO from corrosion and the 1D porous structure to improve ion diffusion and prevent structural collapse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(95 citation statements)
references
References 49 publications
0
91
0
Order By: Relevance
“…To address this key issue, extensive studies have been done to develop high-performance electrode materials, including conducting polymers [12,13], heteroatomdoped carbon materials [14][15][16][17][18][19], transition metal phosphates [20], and transition metal oxides/hydroxides [21][22][23][24][25][26][27]. Lin et al [28] reported a nitrogen-doped mesoporous carbon, of which the specific capacitance can reach to 855 F g −1 at 1 A g −1 in 0.…”
Section: Introductionmentioning
confidence: 99%
“…To address this key issue, extensive studies have been done to develop high-performance electrode materials, including conducting polymers [12,13], heteroatomdoped carbon materials [14][15][16][17][18][19], transition metal phosphates [20], and transition metal oxides/hydroxides [21][22][23][24][25][26][27]. Lin et al [28] reported a nitrogen-doped mesoporous carbon, of which the specific capacitance can reach to 855 F g −1 at 1 A g −1 in 0.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Figure S22, Supporting Information, shows the SEM image of CNZO after 5000 cycles. At the same time, we also compare the test results with the reported work previously such as Co3O4/ ZnCo2O4/CuO-1//AC (35.82 Wh kg −1 at 800 W kg −1 ), [68] ZnO/ Co3O4-450//AC (47.7 Wh kg −1 at 750 W kg −1 ), [18] ZICO//N-G (40.5 Wh kg −1 at 750 W kg −1 ), [26] ZIF-NCS//AC (44.8 Wh kg −1 at 794.5 W kg −1 ), [69] ZnCo2O4//AC (52.36 Wh kg −1 at 650W kg −1 ), [70] PFNC//PFN (27.75 Wh kg −1 at 300 W kg −1 ), [71] and ZNCO//AC (35.6 Wh kg −1 at 187.6 W kg −1 ). By calculation, we obtained the energy density and power density of CNZO//PGH HSC, and the calculation results are shown in Figure 7g.…”
Section: Wwwadvelectronicmatdementioning
confidence: 68%
“…Compared with the other materials, metal oxides are favored by researchers because of their low cost and extremely high theoretical specific capacitance. [18] CoO is applied as electrode widely due to its ultra-high theoretical specific capacitance and high redox activity. ZnO is one of the typical semiconductor materials.…”
mentioning
confidence: 99%
“…In the Ni 2p 3/2 spectra, the peaks at a binding energy (BE) of 855.9 and 861.5 eV (Figure e) are both ascribed to Ni II in Ni(OH) 2 . The O 1s peak (Figure S1) at BE=530.9 eV can be assigned to O in the hydroxide ions, and that at BE=532.0 eV corresponds to surface‐adsorbed carbonate anions . Notably, two peaks at BE=168.3 and 169.6 eV occur in the S 2p spectrum of SNO/NF‐2 (Figure e) but are absent in that of NO/NF, which indicates that S in the form of sulfate was present in SNO/NF‐2 .…”
Section: Resultsmentioning
confidence: 97%